Urban Renewal in the Context of Ageing on the Example of Selected European Cities in the Twenty-First Century - Labus, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This article addresses issues of urban renewal in the context of the ongoing process of ageing population in the XXI century. In 2007, the World Health Organization (WHO) has released publication "Global Age-Friendly Cities: A guide', which set out a vision of modern cities - tailored to the needs of all residents, regardless of age, with particular emphasis on the needs of the elderly. The article on the example selected, the aging of European cities and the principles defined by the Age Friendly Cities program of the author shows how innovative measures are being taken to urban renewal.